Aspirin Potentiates LPS-induced Fibrin Formation (FPA) and TNF-α-synthesis in Whole Blood - Osnes, L.T.N.; Haug, K.B. Foss; Joø, G.B.; Westvik, Å.-B.; Øvstebø, R.; Kierulf, P. (Thrombosis and Haemostasis, 2000)
The effect of aspirin on LPS-incubation of whole blood was investigated. Aspirin induced a concentration dependent increase (2.5–5-fold at 5 mM aspirin) in LPS-induced appearance of TNF-α and fibrinopeptide A (FPA) in plasma, despite the concomitant increase in the inhibitory cytokine IL-10. Aspirin substantially raised the levels of LPS-induced TF-mRNA and TNFα-mRNA in monocytes isolated from whole blood. The median ratio for TF-/β-actin mRNA increased from 1.5 ± 0.44 in the presence of LPS-alone, to 2.5 ± 0.51 when 5 mM aspirin was added. The TNFα/β-actin mRNA ratios were 1.8 ± 0.4 and 5.5 ± 2.7 respectively. Addition of exogenous PGE2 before incubation nearly abrogated the effect of aspirin on TNF-α, substantiating the role of PGE2 as a regulator of TNF-α synthesis, whereas the effect on FPA was small. Thus, in the presence of LPS in this whole blood model, aspirin apparently had a pro-inflammatory rather than an anti-inflammatory effect.
Keywords: Aspirin; tissue factor (TF); TNF-α; whole blood